1985
DOI: 10.3354/meps021175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sewage pollution on coral-reef communities

Abstract: Sewage pollution is an increasing problem in tropical marine environments. In this revlew we synthesize present knowledge of the effects of sewage pollution on coral-reef communities, and suggest directions for future research. A wide range of sewage impacts on coral-reef communities has been reported. Little or no impact has been observed on some reefs in well-flushed waters that receive small quantities of effluent, whereas large d~scharges of effluent into poorly-flushed lagoons and bays have caused major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
0
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(153 citation statements)
references
References 53 publications
2
147
0
4
Order By: Relevance
“…Several studies (Atkinson et al, 1995;Grigg, 1995;Steven and Broadbent, 1997;McCook, 1999;Bongiorni et al, 2003) indicated no substantial adverse responses of coral species to elevated nutrients. However, other laboratory and fi eld experiments (Pastorok and Bilyard, 1985;Tomascik and Sander, 1987;Muscatine et al, 1989;Stambler et al, 1991;Jokiel et al, 1994;Koop et al, 2001) have concluded that corals are negatively affected by increased levels of nutrients and that diversity suffers. Numerous in situ observations exemplify the types of shifts from coral dominance to algal dominance that suggest linkages with chronic nutrient loading, including case studies in Hawaii (Littler, 1973;Banner, 1974;Smith et al, 1981;Maragos et al, 1985;Grigg, 1995), Venezuela (Weiss and Goddard, 1977), the Red Sea (Mergener, 1981;Walker and Ormond, 1982), Barbados (Tomascik andSander, 1985, 1987), American Samoa (Green et al, 1997), Reunion Island (Cuet et al, 1988;Naim, 1993), Bermuda (Lapointe and O'Connell, 1989), the Great Barrier Reef (Bell, 1992), the Florida Keys (Lapointe et al, 1994), Martinique , and Jamaica (Goreau et al, 1997;Lapointe et al, 1997).…”
Section: N U M B E R 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Atkinson et al, 1995;Grigg, 1995;Steven and Broadbent, 1997;McCook, 1999;Bongiorni et al, 2003) indicated no substantial adverse responses of coral species to elevated nutrients. However, other laboratory and fi eld experiments (Pastorok and Bilyard, 1985;Tomascik and Sander, 1987;Muscatine et al, 1989;Stambler et al, 1991;Jokiel et al, 1994;Koop et al, 2001) have concluded that corals are negatively affected by increased levels of nutrients and that diversity suffers. Numerous in situ observations exemplify the types of shifts from coral dominance to algal dominance that suggest linkages with chronic nutrient loading, including case studies in Hawaii (Littler, 1973;Banner, 1974;Smith et al, 1981;Maragos et al, 1985;Grigg, 1995), Venezuela (Weiss and Goddard, 1977), the Red Sea (Mergener, 1981;Walker and Ormond, 1982), Barbados (Tomascik andSander, 1985, 1987), American Samoa (Green et al, 1997), Reunion Island (Cuet et al, 1988;Naim, 1993), Bermuda (Lapointe and O'Connell, 1989), the Great Barrier Reef (Bell, 1992), the Florida Keys (Lapointe et al, 1994), Martinique , and Jamaica (Goreau et al, 1997;Lapointe et al, 1997).…”
Section: N U M B E R 3mentioning
confidence: 99%
“…Changes in bottom-up controls and their interactions not only alter the dominance patterns of the major benthic functional groups on coral reefs but, hypothetically, could have profound long-term consequences mediated through structural transformations and chemical modifi cations to reef systems and their herbivorous fi sh populations. In other words, excessive nutrient enrichment not only increases the productivity and biomass of weedy macroalgae via bottom-up controls that alter patterns of competitive dominance but, over the long term, may lead to coral habitat degradation through (1) reduced spatial heterogeneity by overgrowth (Johannes, 1975;Pastorok and Bilyard, 1985;Szmant, 1997) and (2) nighttime anoxic conditions (tolerated by macroalgae, but not by coral competitors and herbivorous predators; Lapointe and Matzie, 1996) that could indirectly reduce top-down grazer effects. Furthermore, fl eshy macroalgal blooms, irrespective of how they are induced, decrease the growth and reproductive capacity of the more structurally complex reef-building corals (Tanner, 1995;Miller and Hay, 1996;Bellwood et al, 2006;Hughes et al, 2007), as well as inhibit coral larval recruitment (Birkeland, 1977;Tomascik, 1991;Ward and Harrison, 1997) and survival (Lewis, 1986;Hughes et al, 1987;Hughes, 1989;Wittenberg and Hunte, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, visual observations of holes created by bioeroders on dead corals at Sampela led to conclude that bioeroder activities, especially those of boring lithophagid bivalves, play a fundamental role in the degradation of this site. Due to the proximity of the Bajo village near Sampela high nutrient and organic matter concentrations could reduce biotic cover and coral diversity, favor invasion by opportunistic organisms like macroborers and increase the destruction rate (Pastorok and Bilyard, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term degradation of coral reef ecosystems has largely resulted from a combination of human factors, including those with local scale impacts, such as poor land use (Sladek-Nowlis, Roberts, Smith & Siriila, 1997;Ramos-ScharrĂłn, Amador & HernĂĄ ndez-Delgado, 2012; Ramos-ScharrĂłn, Torres-Pulliza & HernĂĄ ndez-Delgado, 2015), sedimentation (Pastorok & Bilyard, 1985;Rogers, 1990), eutrophication (Cloern, 2001;DĂ­ az-Ortega & HernĂĄ ndez-Delgado, 2014;Ennis, Brandt, Grimes & Smith, 2016), sewage pollution (Bonkosky, HernĂĄ ndez-Delgado, Sandoz, Robledo et al, 2009;HernĂĄ ndez-Delgado, Sandoz, Bonkosky, Mattei et al, 2010), and fishing (Hawkins & Roberts, 2004). Also, large scale, climate change-related sea surface warming (Hoegh-Guldberg, 1999;Li & Reidenbach, 2014), massive coral bleaching (Miller, Muller, Rogers, Waara et al, 2009), mass coral mortalities (Miller, Waara, Muller & Rogers, 2006), and ocean acidification (Pandolfi, Connolly, Marshall & Cohen, 2011) have resulted in significant biodiversity loss (Jones, McCormick, Srinivasan & Eagle, 2004) and in the alteration of ecosystem functions (Bellwood, Hughes, Folke & Nyström, 2004), benefits (Veron, Hoegh-Guldberg, Lenton, Lough et al, 2009), and resilience (Carilli, Norris, Black, Walsh et al, 2009;Elmhirst, Connolly & Hughes, 2009;Anthony, Maynard, DĂ­ az-Pulido, Mumby et al, 2011).…”
Section: Synergistic Impacts Of Local and Global-scale Factors In Cormentioning
confidence: 99%